Body weight and egg production of Egyptian Gimmizah fowl as affected by month of laying, photoperiodism and dietary calcium level - YAMANI, K A; SAYIAD, GH A EL; SONBOL, S M; ABDELRAZK, M A; HASAB EL-NABY, W A (The Indian Journal of Animal Sciences, 2013)
The 3 photoperiodic treatments of natural day light, continuous light and 16 hr light: 8 hr dark were applied to Gimmizah fowl. Three rations differing only in calcium (2.50,3.25 and 4.00 %) within each photoperiodism were used during 6 successive laying months after first egg was laid on May. Body weight at maturity, some egg production and egg quality trails, some hatching results and feed conversion were reconded.5) affected traits studied except fertility and hatchability percentages. Weights of egg, albumen and yolk were lower during the first 3 laying months than the leter 3 months Feed intake increased gradually from May to July and became constant till October whilethe only wider feed conversion ratio was in May. August-2.S % calcium level imtraction exerted high egg weight average. Photoperiodism significantly (P